2012
DOI: 10.1111/j.1537-2995.2012.03750.x
|View full text |Cite
|
Sign up to set email alerts
|

The mutation spectrum of the JK‐null phenotype in the Chinese population

Abstract: BACKGROUND: This study aimed to analyze the mutation spectrum of the JK‐null phenotype in the Chinese population. The JK gene encoding the Kidd blood group antigen protein and JK*A/JK*B polymorphism caused by a G‐to‐A mutation at nt838 are well described. However, the molecular basis of the JK‐null phenotype in Chinese populations remains unclear. STUDY DESIGN AND METHODS: Sixteen unrelated JK‐null phenotype donors detected by red blood cell urea lysis resistance assay of 201,194 Chinese blood donors were conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 25 publications
(33 reference statements)
2
24
0
Order By: Relevance
“…This rare phenotype has been reported with the highest frequency in Polynesians (0·1–1·4%). In the Chinese populations, the frequency of JK(a‐b‐) in the southern regions is about 1:5000 (10/50 000 in Guangzhou), which is higher than some other reported regions (1:20 000 in Changchun ; 1:25 000 (4/102 760 and 2/48 400) in Shanghai ; 1:17000–1:20 000 (3/52 260 to 2/40 337 ) in Nanjing; not found (0/23 909) in Zhejiang ) using the red blood cell urea lysis resistance assay for screening. Several patients with anti‐Jk3 were also encountered in Guangzhou .…”
Section: Genotyping Studies For the Null Phenotypes Of Rbcsmentioning
confidence: 66%
See 2 more Smart Citations
“…This rare phenotype has been reported with the highest frequency in Polynesians (0·1–1·4%). In the Chinese populations, the frequency of JK(a‐b‐) in the southern regions is about 1:5000 (10/50 000 in Guangzhou), which is higher than some other reported regions (1:20 000 in Changchun ; 1:25 000 (4/102 760 and 2/48 400) in Shanghai ; 1:17000–1:20 000 (3/52 260 to 2/40 337 ) in Nanjing; not found (0/23 909) in Zhejiang ) using the red blood cell urea lysis resistance assay for screening. Several patients with anti‐Jk3 were also encountered in Guangzhou .…”
Section: Genotyping Studies For the Null Phenotypes Of Rbcsmentioning
confidence: 66%
“…At least 50 probands with JK(a‐b‐) phenotype were identified in the Chinese population for JK genotyping analysis (Table ) . Among them, nine mutations of JK gene were found, in which seven mutations occured on the JK*B allele and two on the JK*A allele.…”
Section: Genotyping Studies For the Null Phenotypes Of Rbcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, more than 24 silencing mutations were identified from Jk(a−b−) individuals (Lucien et al , ; Billingsley et al , ; Horn et al , ; Sriwanitchrak et al , ; Guo et al ., ; St‐Louis et al , ; Onodera et al , ), and it appeared to be difficult to type them by using a simple and cheap genotyping method. In contrast, monoclonal anti‐Jk3 produced in this study (HIRO‐294) will be useful method with a cost benefit for confirming the Jk(a−b−) phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Recent molecular genetic studies revealed diversity of JK null alleles having many different mutations (Lucien et al , ; Billingsley et al , ; Horn et al , ; Sriwanitchrak et al , ; Guo et al ., ; St‐Louis et al , ; Onodera et al , ) that appeared to be difficult to identify by conventional genotyping. In accordance with the above observations, anti‐Jk3 is still useful for Jk(a−b−) typing.…”
mentioning
confidence: 99%